GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI PENGGUNAAN OBAT DISMENOREA PADA KELAS 12 SMK NEGERI 1 BASO - Mulyani, Dwi; Haryani, Cindy; Febriyoldini Elwan, Shaula (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2025)
Dysmenorrhea is also called menstrual cramps or menstrual pain. Primary dysmenorrhea is a mild disease that can be cured with self-medication. Self-medication is the behavior of taking one's own medication based on a diagnosis of the symptoms one is suffering from. Self-medication is also part of "self care" which is an effort to maintain health or prevent and overcome disease. This study aims to determine the level of knowledge of self-medication in the use of dysmenorrhoea drugs among grade 12 female students at SMK Negeri 1 Baso. This type of research is descriptive observation using a questionnaire in the form of Google Form as a measuring tool. The number of samples in this study was 51 female students taken using the purposive sampling method. The results of this study showed that the majority of respondents had good knowledge, namely 10 (89.2%), 30 (71.6%) had sufficient knowledge, and 11 (45.6%) had poor knowledge.